STRATEGI PEMASARAN HAJI DAN UMRAH DALAM PERSPEKTIF MARKETING SYARIAH - Enjang Rosidin (CV. Adiba Aisha Amira, 2026)
This study aims to analyze Hajj and Umrah marketing strategies from the perspective of Sharia marketing. The increasingly competitive Hajj and Umrah travel industry requires travel agencies to implement marketing strategies that are effective, professional, and aligned with Islamic values. This research employed a qualitative method using a library research approach through the analysis of various journals, books, and relevant scientific sources. The findings indicate that Sharia marketing strategies in the Hajj and Umrah business emphasize the values of honesty, trustworthiness, transparency, excellent service, and the utilization of digital media as promotional tools. The implementation of Sharia marketing is capable of increasing pilgrims’ trust, customer loyalty, and the positive image of Hajj and Umrah travel agencies. Furthermore, Sharia-based marketing strategies provide solutions for facing the challenges of modern business competition while maintaining Islamic ethical values.